Transfer of Antarctic herb tundra formation components by the kelp gull in the Argentine Islands area (maritime Antarctica) - Parnikoza, I.; Dykyy, I.; Ivanets, V.; Kozeretska, I. A.; Rozok, A.; Kunakh, V. (Ukrainian Antarctic Journal, 2012)
During the last 50 years, the region of western coast of Antarctic Peninsula and adjacent archipelagos, also known as the maritime Antarctic, has experienced notable climate warming. As a result, a spread of two native species of vascular plants, Deschampsia antarctica Desv. and Colobanthus quitensis (Kunth.) Bartl., over previously unoccupied territories has been noted. Birds have been suggested to be partially responsible for this spread. The focus of the present study was to specifically address the vascular plants utilization in nest building by kelp gull (Larus dominicanus) in the Argentine Islands region. During the 2009/2010 season samples from L. dominicanus nests was collected and analyzed. Besides nests, material lost during transfer was also studied. We demonstrated that in the Argentine Islands region D. antarctica and some bryophytes make up the main nest building material for L. dominicanus. Other materials, like lichens and gull feathers, limpet shells are used less frequently. The plants can reestablish upon transfer via vegetative or generative means. Transfer as diaspores may be the case for some terrestrial algae and lichens.